ITO-Free Semitransparent Organic Solar Cells Based on Silver Thin Film Electrodes - Zhizhe Wang; Chunfu Zhang; Dazheng Chen; Shi Tang; Jincheng Zhang; Li Sun; Ting Heng; Yue Hao (International Journal of Photoenergy)
ITO-free semitransparent organic solar cells (OSCs) based on MoO3/Ag anodes with poly(3-hexylthiophene) and [6,6]-phenyl-C61-butyric acid methyl ester films as the active layer are investigated in this work. To obtain the optimal transparent (MoO3)/Ag anode, ITO-free reference OSCs are firstly fabricated. The power conversion efficiency (PCE) of 2.71% is obtained for OSCs based on the optimal MoO3 (2 nm)/Ag (9 nm) anode, comparable to that of ITO-based reference OSCs (PCE of 2.85%). Then based on MoO3 (2 nm)/Ag (9 nm) anode, ITO-free semitransparent OSCs with different thickness combination of Ca and Ag as the cathodes are investigated. It is observed from our results that OSCs with Ca (15 nm)/Ag (15 nm) cathode have the optimal transparency. Meanwhile, the PCE of 1.79% and 0.67% is obtained for illumination from the anode and cathode side, respectively, comparable to that of similar ITO-based semitransparent OSCs (PCE of 1.59% and 0.75% for illumination from the anode and cathode side, resp.) (Sol. Energy Mater. Sol. Cells, 95, pp. 877–880, 2011). The transparency and PCE of ITO-free semitransparent OSCs can be further improved by introducing a light couple layer. The developed method is compatible with various substrates, which is instructive for further research of ITO-free semitransparent OSCs.